Metabolic control of EMT: The role of α-ketoglutarate and IDH1 in the regulation of Snail and tumor invasion - Alserw, Aya; Justus Liebig University Giessen (My University, 2026)
Metastasis, a defining hallmark of cancer, remains the leading cause of mortality among cancer patients. It is a multistep process in which tumor cells undergo epithelial-to-mesenchymal transition (EMT), invade surrounding tissues, disseminate through the circulation, evade immune surveillance, and colonize distant organs. EMT is induced by microenvironmental cues such as transforming growth factor β (TGFβ) and hypoxia, which activate transcription factors (TFs) including SNAI1/2, ZEB1/2, and TWIST1/2 that orchestrate EMT onset and enhance migratory and invasive capacities. EMT and invasion are particularly critical in primary and secondary brain malignancies. Glioblastoma (GBM), as well as brain metastases originating from lung and breast cancers, are characterized by highly aggressive tumor cells that exhibit profound resistance to conventional therapies. Current treatment options, including surgery, chemotherapy, radiotherapy, and targeted agents, yield only modest survival effects. Metabolic rewiring is another hallmark of tumor progression, enabling cancer cells to sustain growth, adapt to adverse microenvironments, and fuel dissemination. Growing evidence points to a reciprocal crosstalk between metabolism and EMT, thus, identifying metabolic vulnerabilities that can disrupt the early steps of metastasis represents a promising strategy for the development of more effective therapies against invasive cancers. α-Ketoglutarate (α-KG), a pleiotropic metabolite, participates in cellular respiration, macromolecule biosynthesis, hypoxia regulation, and epigenetic modulation via the regulation of α-KG–dependent dioxygenases (α-KGDDs), and ATP synthase inhibition. While α-KG has been proposed to exert anti-tumorigenic and anti-aging functions, its mechanistic role in EMT regulation and invasion in GBM, breast, and lung cancers remains insufficiently defined. In this study, we demonstrated that TGFβ treatment consistently upregulated Snail, but not other EMT TFs, thereby driving invasion in GBM, lung and breast carcinoma models. Supplementation with α-KG reduced Snail expression at RNA and protein levels, impaired EMT induction, and suppressed invasion, while leaving proliferation largely unaffected. To examine the impact of α-KG modulation on EMT regulation, we manipulated isocitrate dehydrogenase 1 (IDH1)-expression, a major source for α-KG in cells. While we detected highly elevated Snail levels and enhanced invasive phenotype following IHD1 depletion, IDH1 overexpression downregulated Snail and HIF-α levels. Importantly, Snail depletion abrogated the invasive phenotype of IDH1-deficient cells, confirming its essential role. We further identified MMPs and collagens as potential downstream mediators of Snail-driven invasion. Mechanistically, α-KG regulated Snail expression on several levels. At the chromatin level, α-KG supplementation reduced active histone marks and modestly increased repressive marks on the SNAI1 promoter. On the signaling and transcriptional levels, α-KG inhibited the ATP synthase-mTORC1-c-Myc axis alongside the established PHD-HIF pathway, converging on Snail transcriptional repression. Consistently, knockdown of HIF-α and c-Myc counteracted the activating effect of IDH1 depletion on Snail promoter function under TGFβ or hypoxic stimulation. Using tumorsphere cultures, we validated the opposing effects of TGFβ and α-KG on tumor invasion. Additionally, we identified TGFβ as a regulator of enzymes controlling α-KG metabolism, possibly linking microenvironmental signaling to α-KG availability and suggesting a feedback loop between the tumor microenvironment and metabolic regulation of EMT. Finally, the prognostic impact of IDH1 and Snail was evaluated using statistical analyses of patient survival data. Low IDH1 and high Snail expression were significantly associated with poor overall survival in patients across GBM, breast, and lung cancers, underscoring the clinical relevance of our findings. Taken together, our work identifies α-KG as an anti-tumorigenic metabolite that suppresses EMT and invasion across multiple tumor models by converging epigenetic and metabolic mechanisms on Snail regulation. Our findings reveal a previously unrecognized feedback link between microenvironmental signaling, metabolic rewiring, and transcriptional control of EMT. By delineating this IDH1-α-KG-Snail axis, the study identifies a metabolic vulnerability underlying EMT induction that could be therapeutically exploited to limit invasion and metastatic dissemination of primary and secondary brain tumors.
Keywords: ddc:610